Evidence-Based Practices in Child and Family Services - Mattox, Teryn (RAND Corporation, 2014)
This document was produced by the Promising Practices Network (PPN) on Children, Families and Communities and was originally published online in 2013 as part of PPN's Issue Brief series. This brief provides an overview of evidence-based practices in child and family services, including definitions and criteria for identifying them. The document also lists resources about effective programs that improve outcomes for children and their families.